Preservation of Makapuno (cocos nucifera L.) through trehalose drying technology - Sartagoda, Kristel June D. (2011)
This study was done to develop dried and instant version of makapuno by using trehalose as pre-treatment agent and vacuum drying. Drying significantly reduces the weight of samples making storage and distribution more convenient, sufficing the need for an alternative method in preserving perishable food such as makapuno. Three trehalose pre-treatment solutions were prepared.: 5% (w/w), 10% (w/w), and 15% (w/w). Preference Ranking Test was used to determine which of the three pre-treatment solutions were most preferred and Friedman test was used to analyze the responses. The 5%(w/w) trehalose solution was most preferred and was chosen as the final pre-treatment solution. Acceptability testing was conducted to compare the sensory characteristics of the fresh and the trehalose-treated samples. Results of the z-test indicated that the reconstituted samples pre-treated with 5% trehalose solution were significantly different from the fresh samples and had a higher acceptability. An accelerated storage study was conducted to establish the product's theoretical shelf-life. Samples were stored in incubators controlled at 3- degrees celcius and 35 degrees celcius. The 0.5% FFA was used as an index for product unacceptability. Samples stored at 30degrees celcius reached the critical FFA value within 24 days and samples stored at 35 degrees celcius reached the critical FFA value within 14 days. The rate constant at each test temperature was calcualted and an Arrhenius plot was constructed. A best fit line was drawn and the value at the target storage temperature of 20 degrees celcius was extrapolated. calculations showed that the products would have reached unacceptability levels within approximately 57 days at 20 degrees celcius packed in HDPE bags. It is recommended that microbial characterization and tests on the gas permeability characteristics of the packaging material be done to analyze the effects of storage conditions to the package integrity and product quality.